Understanding bladder cancer risk: Mendelian randomization analysis of immune cell and inflammatory factor influence - Un, Hiocheng; Wusimanjiang, Wumier; Zhan, Wenhao; Zhang, Xinxin; Li, Minghao; Lei, Jiahao; Lin, Renxuan; Zhang, Yuliang; Chen, Junxing; Wang, Zongren (Frontiers in Immunology, 2024)
Introduction The intricate roles of immune cells and inflammatory factors in cancer, particularly their association with the risk of bladder cancer, are not well understood. Methods This study aimed to clarify potential causal relationships between these elements and the development of bladder cancer using genome-wide association study (GWAS) summary statistics for 731 immune cell phenotypes and 91 circulating inflammatory factors (cases=2,053; controls=287,137). The primary analytical approach was Inverse Variance Weighting (IVW), supplemented by MR-Egger regression, weighted median, and weighted mode analyses. Sensitivity analyses included Cochran Q test, MR-Egger intercept test, and Leave-one-out test. Results The findings indicated that monocytes are positively correlated with an increased risk of bladder cancer. On the contrary, double-negative (DN) T cells, HLA DR+CD8br, and CD28 on CD28+CD45RA+CD8br T cells exhibited an inverse correlation, suggesting a possible protective effect. Furthermore, inflammatory factors IL-20, IL-22RA1, and Eotaxin were significantly associated with an increased risk of bladder cancer. Discussion These results suggest that certain immune cell phenotypes and inflammatory factors may play a role in the development of bladder cancer and could serve as potential biomarkers for assessing tumor risk. The findings also offer new insights into the pathogenesis of bladder cancer, indicating a need for further investigation.